Fundamentals of corporate finance - Brealey, Richard A.; Myers, Stewart C.; Marcus, Alan J. (New York, NY : McGraw Hill Education, 2020)
'Fundamentals of Corporate Finance', by Brealey, Myers and Marcus, provides students with a solid framework of theory and application to use well after they complete the course. This author team is known for their outstanding research, teaching efforts, and world-renowned finance textbooks, so it's no surprise that they provide clear exposition of difficult material without sacrificing up-to-date, technically correct treatments.
Includes bibliographical references and index.
BBS
Karim International
Keywords: Corporations -- Finance; Business & finance